The Attitudes and Self-Efficacy of English Department Students Towards the Use of Mobile Phones for Learning Language - Amir, Verawati (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to know the students’ attitudes and self-efficacy toward the use of mobile phones as a means of learning a language. Descriptive quantitative was used in this research to address the stated questions. Seventy-three samples were taken at the English Education Department by using a stratified random sampling technique. The instrument used was only a questionnaire with close-ended questions, which contained a 5-point scale. The researcher collected data using a questionnaire adapted and modified from previous studies. The researcher did a pilot study to try out a certain research instrument to check the validity and reliability of the questionnaire. After collecting the data, the data is analyzed using descriptive statistics. This research found that the students’ attitudes towards mobile phones as a means for learning a language were found with an overall percentage is 78.6%. The students’ self-efficacy was also reported as having an overall percentage of 80.9%. It summed up that students had positive attitudes toward the potential of mobile phones that help them keep great at solving problems faced in learning a language. Despite that, the high level of self-efficacy in utilizing mobile phones for learning purposes revealed that students could face any problem for learning the languages even had to use mobile phones